2012
DOI: 10.1016/j.jgeb.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of glypican-3 in the early diagnosis of hepatocellular carcinoma among Egyptian patients

Abstract: The aim was evaluation of the role of glypican-3 (GPC3) in early diagnosis of hepatocellular carcinoma (HCC) among Egyptian patients associated with hepatitis C virus (HCV) where genotype 4a is prevalent, as well as differentiating HCC from benign chronic liver disease.Methods: 80 individuals were enrolled in the study: 14 healthy volunteers, 18 patients with HCV, 18 patients with liver cirrhosis (LC) and 30 patients with HCC. Serum GPC3 and AFP levels were measured using ELISA technique.Results: GPC3 at cut-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The positive expression rates in HCC tissues can reach 70–90% and 40–60% in serum, with the specificity more than 90%. GPC3 may have a better utility value in detecting small and early HCC than AFP . The combined use of serum GPC3 and AFP can significantly increase the sensitivity of the diagnosis up to 80% since there may be an approximately 40% rate of GPC3‐positive but AFP‐negative diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…The positive expression rates in HCC tissues can reach 70–90% and 40–60% in serum, with the specificity more than 90%. GPC3 may have a better utility value in detecting small and early HCC than AFP . The combined use of serum GPC3 and AFP can significantly increase the sensitivity of the diagnosis up to 80% since there may be an approximately 40% rate of GPC3‐positive but AFP‐negative diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…However, on univariate analysis, the baseline levels of many candidate markers were associated with the HCC risk. Multivariate regression analysis revealed that only albumin, GPC3, AFP, and total bilirubin retained significance a Similar GPC3 were previously used [16,17] and this cutoff was obtained by the ROC curve analysis b AFP cutoff exactly as originally described [18] c GPC-HCC model = 0.517 + 0.018 × GPC3 (ng/ml) + 0.108 × logAFP (U/L) + 0.025 × total bilirubin (mg%) -0.233 × albumin (g/dl) when combined with each other. This finding and the ROC curve analysis proved that these blood markers are independent predictive variables for HCC.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, the ROC analysis shows that the optimum model diagnostic cutoff value for HCC versus non-HCC was zero. The optimum cutoff for GPC3 was 6 ng/ml, and the similar small cutoff values were previously used [16,17], while it was 400 U/L for AFP, exactly as originally described [18]. The model AUC values for HCC versus liver fibrosis, cirrhosis, and all non-HCCs (fibrosis and cirrhosis combined) were 0.971, 0.905, and 0.939, respectively (Fig.…”
Section: Diagnostic Performance Of Candidate Markers and Model Develomentioning
confidence: 69%
“…In a previous study by Zakhary et al, 2012 [29], among Egyptian patients with HCC on top of CHC, the sensitivity and specificity of AFP for differentiating Open Journal of Gastroenterology Figure 1. ROC curve analysis shows higher AUROC of GPC3 for prediction of HCC than that of AFP (0.92 vs 0.78).…”
Section: Discussionmentioning
confidence: 87%